Middlemarch - Eliot, George, 1819-1880.; Ashton, Rosemary, 1947- (London : Penguin, 2003)
Set in a provincial Victorian neighborhood, the author explores the complex social relationship and the struggle to hold fast to personal tragedy in a materialistic environment.
Originally published: 1994.
Keywords: Coming of age -- Fiction; Great Britain -- History -- Fiction; Great Britain -- Social life and customs -- Fiction